Identifying Patient Access Barriers for Tumor Necrosis Factor Alpha Inhibitor Treatments in Rheumatoid Arthritis in Five Central Eastern European Countries - Inotai, András; Tomek, Dominik; Niewada, Maciej; Lorenzovici, László; Kolek, Martin; Weber, Jakub; Kurrat, Anne-Katrin; Kiss, Emese Virág; Kaló, Zoltán (Frontiers in Pharmacology, 2020)
Introduction: Although there is a significant utilization gap of biologic medicines in the EU, many studies estimate equity in patient access to biopharmaceuticals only based on their availability on the national list of reimbursed medicines. Hidden access barriers may facilitate financial sustainability of pharmaceuticals in less affluent EU countries; however, they have rarely been documented in scientific publications. Our objective was to explore these access barriers for tumor necrosis factor (TNF) alpha inhibitors in rheumatoid arthritis (RA) in 5 Central and Eastern European countries. Methods: A detailed interview guide was developed based on multi-stakeholder workshops and a targeted literature review. In each participant country 3-3-3-3 interviews with payers, rheumatologists, patients/patient representatives and industry representatives were conducted. Responses were aggregated at a country level and validated by primary investigators in each country. Results: Limited number of RA centers and consequently significant travelling time and cost for patients in distant geographical areas, uneven budget allocation among centers, limited capacity of nurses, narrowed patient population in national financial protocols compared to international clinical guidelines in initiating or continuing biologics, high administrative burden in prescribing biologics and limited health literacy of patients were the most relevant barriers to timely patient access in at least three participant countries. Conclusion: Assessing only the availability of TNF alpha inhibitors on the national list of reimbursed medicines provides limited information about real-world patient access to these medicines. Revealing hidden access barriers may contribute to initiate policy actions which could reduce inequity in patient access.